2012
DOI: 10.6061/clinics/2012(06)12
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acute magnesium loading on the maximal exercise performance of stable chronic obstructive pulmonary disease patients

Abstract: OBJECTIVE:The potential influence of magnesium on exercise performance is a subject of increasing interest. Magnesium has been shown to have bronchodilatatory properties in asthma and chronic obstructive pulmonary disease patients. The aim of this study was to investigate the effects of acute magnesium IV loading on the aerobic exercise performance of stable chronic obstructive pulmonary disease patients.METHODS:Twenty male chronic obstructive pulmonary disease patients (66.2±8.3 years old, FEV1: 49.3±19.8%) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…31 The whole world is now fighting against the COVID-19 pandemic. Total hospital stay (days) 7 (5-10) 8 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15) .08…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 The whole world is now fighting against the COVID-19 pandemic. Total hospital stay (days) 7 (5-10) 8 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15) .08…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous or inhalational MgSO 4 promotes bronchodilation, improves lung functions, and reduces the rate of admission to the emergency department during asthmatic crisis. [4][5][6] MgSO 4 reduces lung hyperinflation and improves respiratory muscle strength in stable COPD 7 ; however, its efficacy during the acute exacerbation of COPD is still controversial. 8 During GA, patients with COPD are at a higher risk of developing atelectasis and pneumonia and of requiring prolonged intubation, mechanical ventilation, and prolonged hospital stay and they exhibited a higher mortality rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown that it has the ability to induce both vasodilatory and bronchodilatory effects. 34 Both of these mechanisms have the capacity to potentiate oxygen transport and utilization in the tissues. Enhancing oxygen delivery to the tissue may abate ischemia or reduce the intensity.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Body magnesium is consumed during physical activities which results in negative effects on energy metabolism and physical activity and some athletes use magnesium supplements for their optimal performance. [9,10] In line with…”
mentioning
confidence: 87%